2006
DOI: 10.1108/03090560610657903
|View full text |Cite
|
Sign up to set email alerts
|

Consumer‐based brand equity and country‐of‐origin relationships

Abstract: Purpose -The objective of the present research is to examine the impact of the country of origin of a brand on its consumer-based equity. Design/methodology/approach -Brand equity was conceptualized in this paper as a combination of brand awareness, brand associations, perceived quality and attitudinal brand loyalty. A doubly multivariate design was incorporated in a structured questionnaire to collect data via mall intercepts in an Australian capital city. Findings -Multivariate analysis of variance of the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
262
1
30

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(310 citation statements)
references
References 49 publications
17
262
1
30
Order By: Relevance
“…Aaker (1991) and Keller (2003a) highlighted that COO generates secondary associations for brands and attributes, so that associations and beliefs related to the country can be transferred to the brand itself (Keller, 2003b). In a study asking consumers to evaluate five brand (and organizational) associations, Pappu et al (2006) found that COO did influence their brand associations, confirming previous findings. Thus COO can affect brand consumers' evaluation, because people attach stereotypical perceptions about a country to the products, and this influences first their perception and then, as a consequence, their purchase and consumption behaviour.…”
Section: Literature Reviewsupporting
confidence: 76%
“…Aaker (1991) and Keller (2003a) highlighted that COO generates secondary associations for brands and attributes, so that associations and beliefs related to the country can be transferred to the brand itself (Keller, 2003b). In a study asking consumers to evaluate five brand (and organizational) associations, Pappu et al (2006) found that COO did influence their brand associations, confirming previous findings. Thus COO can affect brand consumers' evaluation, because people attach stereotypical perceptions about a country to the products, and this influences first their perception and then, as a consequence, their purchase and consumption behaviour.…”
Section: Literature Reviewsupporting
confidence: 76%
“…Kim (1995) assumed that a positive country image would lead to favourable brand popularity, and consequently enhances brand commitment and loyalty. It was also demonstrated by certain scholars (Paswan et al, 2003;Pappu, Quester, & Cooksey, 2006) that customer loyalty towards brands originating from favourable country image could develop according to their experience of certain brands that provide quality products. Based on the discussion made above, the following hypotheses are presented:…”
Section: Country Of Originmentioning
confidence: 99%
“…Pappu et al (2006) said that brand equity changes as per the change in COO of the product, further argues that marketing managers who operates in the international arena must comprehend the importance of incorporating COO for brand equity measurement. Consumers develop their preference on the basis of foreign and domestic products (Bankole et al, 2014;Knight, 1999;Kumara and Canhua, 2010).…”
Section: Country Of Originmentioning
confidence: 99%